Skin barrier impairment at birth predicts food allergy at 2 years of age. - IRVINE, ALAN (My University, 2016)
Background Transcutaneous exposure to food allergens can lead to food sensitisation (FS)/food allergy (FA). We measured skin barrier function in early infancy and related it to the later development of FS/FA at 2 years. Methods Infants in the BASELINE birth cohort had transepidermal water loss (TEWL) measured in the early newborn period and at 2 and 6 months. At 2 years, infants had FS/FA screening using skin prick testing and oral food challenge (OFC). Results 1903 infants were enrolled. 1355 were retained to 2 years, 1260 underwent FS screening. 6.27% had FS (79/1260, 95% CI 4.93 – 7.61%), FA prevalence was 4.45% (56/1258, 95%CI 3.38-5.74). Egg was the most prevalent allergen (2.94%), then peanut (1.75%) and cow’s milk (0.74%). Day 2 upper quartile TEWL (>9gwater/m2/hr) was a significant predictor of FA at 2 years (OR 4.1 95% CI 1.5-4.8). 75% of children with FA at 2 years had day 2 TEWL values in the upper quartile. Even in those without atopic dermatitis, infants with upper quartile day 2 TEWL were 3.5 times more likely to have FA at 2 years than infants in the lowest quartile. (CI 1.3 -11.1, p=0.04). Conclusion Neonatal skin barrier dysfunction predicts FA at two years, supporting the concept of transcutaneous allergen sensitisation even in infants who do not develop atopic dermatitis. TEWL could be used for stratifying infants in the first few days of life, before development of 3 atopic dermatitis or food allergy, for targeted intervention studies to potentially alter the atopic march.
PUBLISHED
Keywords: Infant; Prediction; Food Allergy; Food Sensitisation; Atopic Dermatitis; TEWL; Skin Barrier